2000
DOI: 10.1523/jneurosci.20-04-01529.2000
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic-Evoked Synaptic Interactions in Barrel Cortex Revealed by Optical Imaging

Abstract: We used optical imaging of voltage-sensitive dye signals to study the spatiotemporal spread of activity in the mouse barrel cortex, evoked by stimulation of thalamocortical afferents in an in vitro slice preparation. Stimulation of the thalamus, at low current intensity, results in activity largely restricted to a single barrel, and to the border between layers Vb and VI. Low concentrations of the GABA A receptor antagonist bicuculline increase the amplitude of the optical signals, without affecting their spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 79 publications
(104 reference statements)
7
84
0
Order By: Relevance
“…Sparse intercolumnar connections also target the supragranular branches of apical dendrites belonging to layer IV star pyramids (Schubert et al, 2003), and these mediate weak synaptic interactions (Feldmeyer et al, 1999;Petersen and Sakmann, 2000;Schubert et al, 2003). In addition, analyses of voltagesensitive dye signals fail to demonstrate direct interbarrel pathways (Laaris et al, 2000;Laaris and Keller, 2002;Petersen et al, 2003). Finally, under the light narcosis used here, AW responses are unaffected by lesions of adjacent barrels (Goldreich et al, 1999).…”
Section: Receptive Field Sizesmentioning
confidence: 79%
“…Sparse intercolumnar connections also target the supragranular branches of apical dendrites belonging to layer IV star pyramids (Schubert et al, 2003), and these mediate weak synaptic interactions (Feldmeyer et al, 1999;Petersen and Sakmann, 2000;Schubert et al, 2003). In addition, analyses of voltagesensitive dye signals fail to demonstrate direct interbarrel pathways (Laaris et al, 2000;Laaris and Keller, 2002;Petersen et al, 2003). Finally, under the light narcosis used here, AW responses are unaffected by lesions of adjacent barrels (Goldreich et al, 1999).…”
Section: Receptive Field Sizesmentioning
confidence: 79%
“…This finding is further supported by optical recordings of voltage-sensitive dyes, which have shown that excitatory activity evoked by stimulation of thalamocortical afferents is largely restricted to a single barrel whereas in layer 2/3 it spreads across cortical columns (Laaris et al, 2000). It may be speculated that in layer 2/3 excitation arriving from layer 4 is distributed by pyramidal cell axons throughout the primary somatosensory cortex in vertical and horizontal directions (for review, see DeFelipe and Farinas, 1992).…”
Section: Supragranular Layersmentioning
confidence: 81%
“…3). Thus, the intercolumnar synchronization in layer II/III seems to be strictly controlled by GABA A inhibition (Laaris et al, 2000;Petersen and Sakmann, 2001;Laaris and Keller, 2002), which is likely to operate in a feedforward manner after activation of layer II/III pyramidal neurons in the home column by the inputs arising from layer IV.…”
Section: Discussionmentioning
confidence: 99%
“…In the rodent barrel cortex, a distinct topographical representation of the whisker is well known (Woolsey and Van der Loos, 1970;Moore et al, 1999), and the presence of columnar organization is most apparent in this area as revealed by the barrel structure of layer IV (Feldmeyer et al, 1999(Feldmeyer et al, , 2005Laaris et al, 2000;Lubke et al, 2000;Sakmann, 2000, 2001;Bender et al, 2003). In contrast, in the primary gustatory area of the insular cortex, the topographical representation of the four basic tastes (sweet, sour, salty, and bitter) appears to be much less distinct (Yamamoto et al, 1980(Yamamoto et al, , 1984(Yamamoto et al, , 1985Kosar et al, 1986;Ogawa et al, 1991Ogawa et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%